Spectral tuning and evolution of primate short-wavelength-sensitive visual pigments - Carvalho, Livia S. (The Royal Society, 2012)
The peak sensitivities (λ(max)) of the short-wavelength-sensitive-1 (SWS1) pigments in mammals range from the ultraviolet (UV) (360–400 nm) to the violet (400–450 nm) regions of the spectrum. In most cases, a UV or violet peak is determined by the residue present at site 86, with Phe conferring UV sensitivity (UVS) and either Ser, Tyr or Val causing a shift to violet wavelengths. In primates, however, the tuning mechanism of violet-sensitive (VS) pigments would appear to differ. In this study, we examine the tuning mechanisms of prosimian SWS1 pigments. One species, the aye-aye, possesses a pigment with Phe86 but in vitro spectral analysis reveals a VS rather than a UVS pigment. Other residues (Cys, Ser and Val) at site 86 in prosimians also gave VS pigments. Substitution at site 86 is not, therefore, the primary mechanism for the tuning of VS pigments in primates, and phylogenetic analysis indicates that substitutions at site 86 have occurred at least five times in primate evolution. The sole potential tuning site that is conserved in all primate VS pigments is Pro93, which when substituted by Thr (as found in mammalian UVS pigments) in the aye-aye pigment shifted the peak absorbance into the UV region with a λ(max) value at 371 nm. We, therefore, conclude that the tuning of VS pigments in primates depends on Pro93, not Tyr86 as in other mammals. However, it remains uncertain whether the initial event that gave rise to the VS pigment in the ancestral primate was achieved by a Thr93Pro or a Phe86Tyr substitution.